QT PRODACT: Usability of Miniature Pigs in Safety Pharmacology Studies: Assessment for Drug-Induced QT Interval Prolongation - Mayumi Kano; Tohru Toyoshi; Sakae Iwasaki; Masami Kato; Masayoshi Shimizu; Takao Ota (Elsevier, 2005)
To investigate whether miniature pigs are useful for evaluating the potential of drugs for drug-induced prolongation of the QT interval, we performed an in vivo QT assay using conscious and unrestricted miniature pigs. Compared with the vehicle average baseline values, haloperidol at 3 and 10 mg/kg, p.o. prolonged the QTcF interval (Fridericia's formula) by 8% - 16%. The plasma concentration of haloperidol at which QT interval was prolonged (Cmax = 42.9 ng/mL) was almost equal to that in humans. dl-Propranolol at 3, 10, and 30 mg/kg, p.o. caused no alterations in QT interval. dl-Propranolol at 3, 10, and 30 mg/kg, at which plasma concentrations were lower than in humans treated with dl-propranolol at the therapeutic dose level, shortened QTcF interval by 7% - 12%. dl-Sotalol at 10 mg/kg, p.o. prolonged QTcF interval by 7%. From the above results, we considered that the miniature pig can be used for prediction of drug-induced prolongation of QT interval in humans, and thus, it is one of the useful animal species for assessing electrocardiograms in safety pharmacology studies. Keywords:: haloperidol, dl-propranolol, dl-sotalol, miniature pig, QT interval